Squamous cell carcinoma of the skin in a 14-year-old boy. - Conese, M. (European Journal of Pediatric Dermatology, 2018)
Squamous cell carcinoma (SCC) is a skin tumor characteristic of the adults. A case of SCC affecting a 14-year-old boy is reported. The case is reported because of the rarity at this age, the site which is not common for squamous cell carcinoma and finally the interesting pathogenetic mechanisms responsible far the neoplasia.